Value co‐creation and co‐destruction behaviour: Relationship with basic human values and personality traits. (3rd November 2021) - Ogunbodede, Olabode; Papagiannidis, Savvas; Alamanos, Eleftherios
Abstract: Service systems create value when actors exhibit behaviours expected to facilitate resource integration and could destroy value when actors do not exhibit the expected set of behaviours. This study seeks to determine which groups of values and individual traits facilitate consumer co‐creation and co‐destruction behaviours. A data set of 390 online survey responses from consumers in the United States was analysed using multiple regression. The analysis suggests that values which express self‐enhancement and openness‐to‐change are most likely to facilitate co‐destruction behaviour, while values which express self‐transcendence and conservation are most likely to facilitate co‐creation behaviour. With regards to traits, we find that neurotic traits are most likely to facilitate co‐destruction behaviour and least likely to facilitate co‐creation behaviours. Conscientious and agreeable traits are least likely to facilitate co‐destruction behaviours, while extraversion and openness traits are most likely to facilitate co‐creation behaviours. This study contributes to the literature by providing a better understanding of the consumer values and traits which facilitate co‐destruction and co‐creation behaviour. This study also shows that the basic human values circumplex structure can be divided to reflect co‐destruction and co‐creation values. The polar opposites of the big five personality traits can be classified based on their tendencies to co‐destroy or co‐create value.